Drying characteristic of ipil-ipil firewood - Figueroa, Arturo Mariano I. (Arturo Mariano Isip) 1960- (1986)
Drying tests were conducted with small branches of giant ipil-ipil (leucaena leucocephala) at two levels of dry-bulb temperatures, 120 deg.F and 140 deg.F Each test was represented with unbarked and debarked fire wood samples. The diffusion coefficients of each sample were determined using the experimental data and the diffusion model equation for homogenous infinite cylinder (Crank, 1956). These coefficients were then used to generate theoretical drying curves. The results showed that the diffusion coefficients of debarked firewood sample can be treated as a constant whereas the diffusion coefficients of the unbarked firewood sample significantly varies with time. Moreover, the average diffusion coefficient (D/AV) for the debarked firewood sample indicated a good fit between the theoretical and experimental drying curves. The model equation is found to be not valid to describe the drying process in the unbarked sample.
Thesis (M.S. Energy Engineering)--University of the Philippines Diliman.
Typescript.
Vita.
Keywords: Ipil-ipil.; Drying; Ipil-ipil as fuel